PCR Multiplexing Based on a Single Fluorescent Channel Using Dynamic Melting Curve Analysis - Zhang, Haoqing; Gaňová, Martina; Yan, ZhiQiang; Chang, Honglong; Neužil, Pavel (ACS omega, 2020)
Since its invention in 1986, the polymerase chain reaction (PCR), has become a well-established method for the detection and amplification of deoxyribonucleic acid (DNA) with a specific sequence. Incorporating fluorescent probes, known as TaqMan probes, or DNA intercalating dyes, such as SYBR Green, into the PCR mixture allows real-time monitoring of the reaction progress and extraction of quantitative information. Previously reported real-time PCR product detection using intercalating dyes required melting curve analysis (MCA) to be performed following thermal cycling. Here, we propose a technique to perform dynamic MCA during each thermal cycle, based on a continuous fluorescence monitoring method, providing qualitative and quantitative sample information. We applied the proposed method in multiplexing detection of hepatitis B virus DNA and complementary DNA of human immunodeficiency virus as well as glyceraldehyde 3-phosphate dehydrogenase in different concentration ratios. We extracted the DNA melting curve and its derivative from each PCR cycle during the transition from the elongation to the denaturation temperature with a set heating rate of 0.8 K·s-1and then used the data to construct individual PCR amplification curves for each gene to determine the initial concentration of DNA in the sample. Our proposed method allows researchers to look inside the PCR in each thermal cycle, determining the PCR product specificity in real time instead of waiting until the end of the PCR. Additionally, the slow transition rate from elongation to denaturation provides a dynamic multiplexing assay, allowing the detection of at least three genes in real time.